The Relationship between Performance Accomplishment and Physiological Emotional State with Adaptation among Patients with Diabetes Mellitus - Risa Setia Ismandani; Warsini Warsini; Dwi Yuniar Ramadhani; Siti Hardiyanti (Adi Husada Nursing Journal, 2025)
Diabetes Mellitus (DM), as a major non communicable disease, continues to pose a global health challenge due to its rapidly increasing prevalence. In Indonesia, approximately 11.3% of the adult population is affected by diabetes. The chronic nature of DM substantially influences patients’ quality of life across physical, psycho logical, social, and role-related domains. Consequently, effective DM management requires not only medical treatment but also psychosocial support to enhance patients’ adaptive capacity. This study aimed to examine the relationship between performance accomplishment and physiological emotional state and overall adaptation among patients with Diabetes Mellitus. A correlational cross-sectional design was employed involving 145 patients with type 2 DM recruited from Jayengan Primary Health Center (Surakarta) and Tambak Rejo Primary Health Center (Surabaya). Data were collected using self-efficacy source questionnaires and an adaptation instrument based on Roy’s Adaptation Model. Multiple linear regression analysis revealed that performance accomplishment was significantly associated with patient adaptation (B = 8.110; β =0.394; p = 0.001), as was physiological–emotional state (B = 6.765; β = 0.286; p =0.001). Performance accomplishment emerged as the most dominant contributor to adaptation. These findings highlight the importance of DM management interventions that prioritize gradual mastery experiences and emotional support to strengthen patients’ adaptive responses.